PERBANDINGAN HASIL BELAJAR FISIKA MELALUI METODE EKSPERIMEN INKUIRI DENGAN VERIFIKASI BERBASIS KETERAMPILAN PROSES SAINS - Anna Yunizea; Agus Suyatna; Abdurrahman - (Jurnal Pembelajaran Fisika, 2012)
Science process skills are one of important factor in improving students’ learning outcomes. This study aims to determine the average difference in learning outcomes of cognitive and psychomotor aspects of the students in learning physics on the use of approach with inquiry experimental method and verification experiment. The learning outcomes of cognitive aspects were measured by pretest and posttest results, while for the psychomotor aspects were measured by the achievement of the skill aspects. The technique used in data analysis was N-gain while the hypothesis testing used Independent Sample t-Test. Based on the average scores of N-gain average, cognitive aspects of student learning outcomes in the first experimental class was 0.52 and the second experimental class was 0.33. These results indicate that the science process skill approach with experimental inquiry method is more effective to be applied to improve student learning outcomes in the cognitive aspects of learning. In the psychomotor aspect, the average value of inquiry experimental class was 73.77 and 70.03 for verification experiment. Furthermore, there is no difference in the average results of the psychomotor aspects of student learning through inquiry and verification experimental method based on science process skill.Keywords: science process skills, experimental inquiry, experimentalverification, learning outcomes